2020
DOI: 10.3311/ppci.15457
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Hydrophobic Additives in Moisture Damage Reduction of Asphalt Mixtures

Abstract: In order to increase the life of the asphalt mixture and reduce the cost of the pavement life cycle, methods must be provided to improve the quality. Accordingly, the effects of aggregate surface coating with hydrophobic material in order to modify the aggregate mixture’s polar properties and reduce its hydrophilic properties are investigated. To this end, limestone and granite aggregates, 60-70 bitumen, and Two types of additives were used as the primary materials for the construction of asphalt mixtures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Various factors affect the occurrence of moisture sensitivity and resistance of a mixture against it, with the structure of minerals which form aggregates being one of the most important ones. Two minerals, SiO 2 and CaO (or CaCO 3 ), induce a substantial change in the hydrophilic or hydrophobic properties of HMA. The higher the percentage of SiO 2 in aggregates, the more hydrophilic it will be.…”
Section: Modified Lottman Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors affect the occurrence of moisture sensitivity and resistance of a mixture against it, with the structure of minerals which form aggregates being one of the most important ones. Two minerals, SiO 2 and CaO (or CaCO 3 ), induce a substantial change in the hydrophilic or hydrophobic properties of HMA. The higher the percentage of SiO 2 in aggregates, the more hydrophilic it will be.…”
Section: Modified Lottman Testmentioning
confidence: 99%
“…However, the presence of water within and between bound layers, specifically asphalt layers, is a relatively recent understanding within the professional community [1]. The bond quality between bitumen-aggregates has a considerable influence on the durability of HMA against moisture sensitivity [2].…”
Section: Introductionmentioning
confidence: 99%
“…The primary investigation was reported in Texas Transportation Institute which revealed that Surface Free Energy (SFE) measurements could be applied as an impressive tool to predict moisture damage and fatigue cracking in asphalt mixtures. Hamedi et al [6] examined the concepts of SFE and its application in asphalt mixtures. The results of his study showed that thermodynamic changed in adhesion and cohesion of SFE were directly related to debonding in the asphalt binder aggregates contact surface and cracks in the mastic.…”
Section: Previous Studiesmentioning
confidence: 99%
“…6 demonstrate the effect of curing and thermal equilibrium time on the final strains of different asphalt mixtures, mixtures constructed by limestone aggregate and 60-70 penetration grade asphalt binder, granite aggregate and 60-70 penetration grade asphalt binder, limestone aggregate and 85-100 penetration grade asphalt binder, and granite aggregate and 85-100 penetration grade asphalt binder.…”
mentioning
confidence: 94%
“…environmental conditions (temperature), vehicle speed, tire contact pressure, and volume of passing traffic can contribute to the occurrence of this type of damage. Most rutting tests are performed at high temperatures as a major part of rutting occurs due to high thermo-sensitivity of asphalt binders and weakness in the stability of asphalt layers at high temperatures [5,6].…”
Section: Introductionmentioning
confidence: 99%